TRANSITIVITY ANALYSIS IN JONATHAN MURRAY CHU’S MOVIE “CRAZY RICH ASIANS” - Elin Istriningsih; Rosyida Ekawati (Jurusan Sastra Indonesia, 2022)
This study aims at explaining the transitivity processes and their effectiveness in Jonathan Murray Chu's Crazy Rich Asians movie. It uses a qualitative method. The data are the utterances of the characters in the Crazy Rich Asians movie. Then, they are categorized and analyzed based on the processes of transitivity and their effectiveness. The types of transitivity processes found in the movie are material processes of action and event, mental processes of perception, cognition and affection, relational processes of identification and attributive, verbal processes, behavioral processes, and existential process. For their effectiveness transitivity components can be measured by ten parameters i.e participant, kinesis, aspect, punctuality, affirmation, mode, agency, affectedness of object, and individuation of object.